High-throughput transcriptome sequencing of the cold seep mussel Bathymodiolus platifrons - Wong, Yue Him (Sci Rep, 2015)
Bathymodiolid mussels dominate hydrothermal vents, cold methane/sulfide-hydrocarbon seeps, and other sites of organic enrichment. Here, we aimed to explore the innate immune system and detoxification mechanism of the deep sea mussel Bathymodiolus platifrons collected from a methane seep in the South China Sea. We sequenced the transcriptome of the mussels’ gill, foot and mantle tissues and generated a transcriptomic database containing 96,683 transcript sequences. Based on GO and KEGG annotations, we reported transcripts that were related to the innate immune system, heavy metal detoxification and sulfide metabolic genes. Our in-depth analysis on the isoforms of peptidoglycan recognition protein (PGRP) that have different cellular location and potentially differential selectivity towards peptidoglycan (PGN) from gram-positive and gram-negative bacteria were differentially expressed in different tissues. We also reported a potentially novel form of metallothionein and the production of phytochelatin in B. platifrons, which has not been reported in any of its coastal relative Mytilus mussel species. Overall, the present study provided new insights into heavy metal and sulfide metabolism in B. platifrons and can be served as the basis for future molecular studies on host-symbiont interactions in cold seep mussels.